2017
DOI: 10.1186/s12913-017-2382-1
|View full text |Cite
|
Sign up to set email alerts
|

Can formalizing links among community health workers, accredited drug dispensing outlet dispensers, and health facility staff increase their collaboration to improve prompt access to maternal and child care? A qualitative study in Tanzania

Abstract: BackgroundIn Tanzania, progress toward achieving the 2015 Millennium Development Goals for maternal and newborn health was slow. An intervention brought together community health workers, health facility staff, and accredited drug dispensing outlet (ADDO) dispensers to improve maternal and newborn health through a mechanism of collaboration and referral. This study explored barriers, successes, and promising approaches to increasing timely access to care by linking the three levels of health care provision.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(60 citation statements)
references
References 15 publications
3
57
0
Order By: Relevance
“…The implication of this is that timely decision on correct intervention towards addressing health problems specifically related to underfive children is important. A study by Dillip et al (2017) conducted in Tanzania, which is in line with the current study, observed that more timely access to appropriate health care is one of the factors contributing to reduction of child and maternal mortality. The current study encourages equally in decision making between male and female to enable timely attainment of treatment when there is a health problem, specifically that of under-fivechildren within agro-pastoralist households.…”
Section: Discussionsupporting
confidence: 56%
“…The implication of this is that timely decision on correct intervention towards addressing health problems specifically related to underfive children is important. A study by Dillip et al (2017) conducted in Tanzania, which is in line with the current study, observed that more timely access to appropriate health care is one of the factors contributing to reduction of child and maternal mortality. The current study encourages equally in decision making between male and female to enable timely attainment of treatment when there is a health problem, specifically that of under-fivechildren within agro-pastoralist households.…”
Section: Discussionsupporting
confidence: 56%
“…‱ Officially recognise retail and community-based providers as an essential part of the public health sector and integrate them into formal health planning [31,66].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the tasks VHTs described within this role have been noted in previous research, including translating from local languages, accompanying clients to the hospital, and improving communication between patients and providers. [35–37] Where this role is supported, VHTs can become significant players in ensuring patients receive high-quality HIV and SRH care [38]. However, this study found that VHTs playing this middle role faced disrespect from medical workers, with some saying that this was the greatest challenge they faced in their HIV and SRH work.…”
Section: Discussionmentioning
confidence: 99%